Diaspora Bugis dan Perkembangan Perdagangan Kopra di Sumatera pada Awal Abad XX (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2020)
This paper will observe the relation between the Buginese diaspora and copra and coconut trading system in sumatera at the early 20th century. The success of buginese dispora to develop their trading system in sumatera had close reletions with their their chain of trade and their expansion to get the land in frontiers. The effect of the expansion have been an increasing commercialisations of economy and the growth of towns largely dependent on trade. To secure Buginese trading chains, their engaged in the growing of coconut for copra. Different from Malay that plant rubber. Inability of the copra trading system become the main trading commodity in Sumatera influenced by the Dutch colonial policy. This condition depent on Buginese trader always played as a opposition to the colonial goverment. They establishing a chains trading with china and England. They had develop singapore as a main port in the malacca strait to reduce the Batavia influences. This political situation show us that commodity trading system can’t sparated with political policy.